Nationwide epidemiological survey of immunoglobulin G4‐related disease with malignancy in Japan. Issue 6 (20th March 2022) - Sumimoto, Kimi; Uchida, Kazushige; Ikeura, Tsukasa; Hirano, Kenji; Yamamoto, Motohisa; Takahashi, Hiroki; Nishino, Takayoshi; Mizushima, Ichiro; Kawano, Mitsuhiro; Kamisawa, Terumi; Saeki, Takako; Maguchi, Hiroyuki; et al.
Abstract: Background and Aim: To clarify the clinicoepidemiological characteristics of immunoglobulin G4 (IgG4)‐related disease (IgG4‐RD) with malignancy, a nationwide epidemiological survey was conducted. Methods: Immunoglobulin G4‐related disease patients with malignancy who had visited selected hospitals in Japan were surveyed. The study consisted of two stages: the number of IgG4‐RD patients with malignancy was estimated by the first questionnaire and their clinicoepidemiological characteristics were assessed by the second questionnaire. Results: The frequencies of autoimmune pancreatitis (AIP), IgG4‐related sialadenitis, IgG4‐related eye disease, IgG4‐related kidney disease, and IgG4‐related retroperitoneal fibrosis were 44.7%, 20.8%, 14.0%, 5.16%, and 5.12%, respectively. The overall prevalence of malignant disease in IgG4‐RD cases was estimated to be 10 900 per 100 000 cases, which was significantly higher than that of malignant disease in the general population. The prevalence of malignant lymphoma in IgG4‐RD cases was the highest and was estimated to be 1985 per 100 000 cases. IgG4‐related kidney disease had the highest frequency of malignant disease (17.1%). In data from 200 patients, 61 (30.5%) cases of cancer were found 2 years or more before the IgG4‐RD diagnosis, 92 cases (46%) during the 1 year preceding or following IgG4‐RD diagnosis, and 62 cases of cancer (31%) 2 or more years following IgG4‐RD diagnosis. Conclusions: The nationwide survey for IgG4‐RD with malignancy in Japan showed that IgG4‐RD may be related with malignant diseases.